POLITICAL SYSTEM REFORM PROCESS IN VIETNAM - Anh, Dr. Nguyen Ngoc (The journal of contemporary issues in business and government, 2021)
The political system in Vietnam follows the former Soviet Union style, which includes the sub-systems of Party, state and mass organizations. It remains almost unchanged since the 1986. While Vietnam has been achieving impressive socio-economic development results, the political system somehow lag behind the socio-economic development process. At present, the political system in Vietnam is relatively heavy, costly and inefficient with many overlapped and/or duplicated funtions/responsibilities across sub-systems and agencies. As a result, the resolution No. 18-NQ/TW dated 25 October 2017 of the Central Committee of the Communist Party of Vietnam (CPV) set the following target by 2021: “to reduce the number of agencies and enhance operational efficiency and effectiveness; reduce commune- level administrative units that are below 50% of standard requirements on population, natural land area and reduce the number of residential blocks”1. After more than three years of implementation, the political system‟s organizational structure and number of permanent staff has changed radically. Key results include: (i) significant reduction of the Party, state and mass organizations; (ii) enhanced efficiency and effectiveness thanks to merging the overlapped agencies and similar positions; (iii) large reduction of administrative units. However, there are many barriers and challenges that require a systematic transformation with strong political will and long-term vision for change toward a modern, efficient and effective political system.